2006
DOI: 10.4049/jimmunol.177.6.4203
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequencies of Cochlin-Specific T Cells in Patients with Autoimmune Sensorineural Hearing Loss

Abstract: Autoimmune sensorineural hearing loss (ASNHL) is the most common cause of sudden hearing loss in adults. Although autoimmune etiopathogenic events have long been suspected in ASNHL, inner ear-specific Ags capable of targeting T cell autoreactivity have not been identified in ASNHL. In this study, we show by ELISPOT analysis that compared with normal hearing age- and sex-matched control subjects, ASNHL patients have significantly higher frequencies of circulating T cells producing either IFN-γ (p = 0.0001) or I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 34 publications
0
59
0
5
Order By: Relevance
“…A role for cochlin in host defense is also possible. Loss-of-function mutations in DFNA9 cause increased susceptibility to infection (de Kok et al, 1999;Baek et al, 2006). Furthermore, a number of DFNA9 patients tend to develop cardiovascular disease .…”
Section: Cochlin and Extracellular Matrixmentioning
confidence: 99%
“…A role for cochlin in host defense is also possible. Loss-of-function mutations in DFNA9 cause increased susceptibility to infection (de Kok et al, 1999;Baek et al, 2006). Furthermore, a number of DFNA9 patients tend to develop cardiovascular disease .…”
Section: Cochlin and Extracellular Matrixmentioning
confidence: 99%
“…Cochlin has also been implicated in autoimmune hearing loss in humans (Boulassel et al 2001;Baek et al 2006) and in experimental immune-mediated hearing loss in mice (Solares et al 2004). Similarly, CTL2 has been implicated in autoimmune hearing loss (Zeitoun et al 2005) and experimental antibodymediated hearing loss (Nair et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…1 He described patients with progressive, bilateral, synchronous or sequential, sensorineural hearing loss who responded to immunosuppressive therapy and who also tested positive for laboratory tests, clinical manifestations and immunological tests prescribed for autoimmune hearing loss. 2 Baek et al 3 demonstrated that patients with AIED have higher frequencies of interferon (IFN)-g-producing T cells and higher serum antibody titers compared with both normal hearing control subjects and patients with noise-and/or age-related hearing loss. Many autoantigens have been implicated as possible causal antigens (Ags) in AIED: heat-shock protein 70, 4,5 collagen II, 6 cochlin 3,7 and, most recently, b-tubulin.…”
Section: Introductionmentioning
confidence: 99%
“…2 Baek et al 3 demonstrated that patients with AIED have higher frequencies of interferon (IFN)-g-producing T cells and higher serum antibody titers compared with both normal hearing control subjects and patients with noise-and/or age-related hearing loss. Many autoantigens have been implicated as possible causal antigens (Ags) in AIED: heat-shock protein 70, 4,5 collagen II, 6 cochlin 3,7 and, most recently, b-tubulin. [8][9][10][11][12][13] Yoo et al [9][10][11] demonstrated that 67 (59%) of 113 patients with Ménière's disease had antibodies to a 55-kDa protein b-tubulin in guinea-pig inner ear extract.…”
Section: Introductionmentioning
confidence: 99%